PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR BIOLOGI KELAS X-7 SMA N 1 BARAT MELALUI PENERAPAN MODEL THINK PAIR SHARE - Nunuk Purwanti (Florea : Jurnal Biologi dan Pembelajarannya, 2015)
Motivation plays an important role in learning, X-7 grade students of SMA Negeri 1 Barat shows the known to be less motivated to follow the teaching of Biology. The aim of research to increase the motivation to learn biology X - 7 grade SMA Negeri 1 Barat with the application Think Pair Share (TPS). This type of research is classroom action research with planning, action, observation, and reflection, material monera and protists conducted in two cycles. Research subject class X-7 SMA Negeri 1 Barat of academic year 2014/2015. The results showed cooperative learning Think Pair Share can help students overcome the problem for expression and enhance self-confidence of students, so as to increase the motivation of students.